If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15z + -2z = 0 Combine like terms: 15z + -2z = 13z 13z = 0 Solving 13z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '13'. z = 0 Simplifying z = 0
| 4(3w-2)=2w+3 | | 14x+46=2 | | .25(12x+16)=16-3X | | 11u-u-14u+13u= | | (4+U)(3U+8)=0 | | 5x+9=-2 | | 2x^2-43x+111=0 | | 43x+111=0 | | y=0.10x+80 | | -8(x-3)+3=27 | | (u-7)(u+4)=1(u-7)(u+2)+(u-5)(u+2) | | 15=5x+10 | | 12-7x=46-21x | | 2z+10=70 | | -x(3x+2)=5 | | 12w^2=28w+5 | | x^4y^2-2x^2y+1=0 | | 4x^2-8x+10=0 | | x^4y^2-2x^2y-1=0 | | -8[-3-(-5+6j)]=4(12j-4) | | 4(w-4)(w-1)-1(w-4)=-5(w-1) | | 8m=3m+2 | | 6x-10y=30 | | 8m=3n+2 | | 4(w-4)(w-1)=-5(w-1) | | -16x^5-36x^3=0 | | (3-5x)-(2x-1)= | | 3t/4-t/2=1 | | -8x-24+2x+6=7x+10 | | 3(v-8)=5v-38 | | X=79x | | -7y+4=8(y+8) |